Water Quality and Water Borne Diseases in India: A Review (Indian Journal of Social Science and Literature (IJSSL), 2024)
Climate change is impacting seriously human lives and human health in varied ways. Environmental pollution like air and water pollution are taking heavy toll on human beings. The increasing demand of water lead to its over exploitation and pollution and inefficient water use policies and methods are due to unchecked population growth and expansion of economic activities. Water quality problems are increasing and so are the water borne diseases. Various laws, policies and programmes are started by governments but the quality of water is deteriorating day by day.